Key Factors Influencing Tourist’s Destination Image: A Perspective From International Tourists in Jordan - Mheidat, Mohammad Zain; Marzuki, Azizan (Dirasat: Human and Social Sciences, 2024)
Objectives: This paper highlights the significant role of key factors in the formation of tourist destination image. From the perspective of international tourists who represent the major target market in Jordan, this study explores the potential influence of destination image on their travel intention and repeat visitation. Understanding factors that motivate tourists to travel to a specific destination can lead to predicting their future decisions. Methods: This study adopts a quantitative approach based on the analysis of selected items of questionnaire responses collected from 180 international tourists who visited Jordan post-COVID-19 pandemic. Results: Findings reveal that the destination image of international tourists is significantly affected by internal and external factors. Perception of tourist attractions, travel experience, interaction with the local community, and feeling of safety and security are crucial in enhancing the image of international tourist destinations. Conclusions: Tourism planners, policymakers, and stakeholders can benefit from the results by using the positive image of Jordan tourism to apply a suitable marketing strategy, investing in security and safety, and preserving the country’s tradition of hospitality. That, in return, will allow tourist destinations to provide a unique experience for visitors, contributing to the growth and development of the economy.